Strategies Applied By English Teacher To Encourage Students To Speak At Tenth Grade Of Senior High School 3 Sukoharjo In Academic Year 2016/2017 - Saraswati, Shalindri; , Aryati Prasetyarini, S.Pd, M.Pd (2017)
This research is aimed at (1) identifying the strategies used by the English teacher to encourage students to speak, and (2) describing the teacher applies the strategies to encourage students to speak. The type of this research is qualitative research. The method of collecting data is interview, observation, and documentation. The result of this research shows that (1) the strategies applied by english teacher to encourage students to speak, the teacher used strategies as follows:1) dividing the students into group randomly, 2) structuring group discussion, 3) hunting tourist, 4) using games, 5) using bilingual in teaching learning for speaking skill, and 6) giving reward; (2) the way of implementing the strategies to encourage students to speak. The researcher concluded that English teacher of Senior High School 3 Sukoharjo used strategies to encourage students to speak which could increase their speaking skill ability.